(untitled) (Proceedings of Southern Federal University. Philology, 2013)
Akhmadulin E. Keywords: system of periodic press, typology of publications, classification of the press, history of journalism, principle of historical analysis, management subject, censorship, publisher, reading audience. The article is devoted to the methodological problems in the study of the regional periodical press of the pre-revolutionary period, mostly referring to the first years of the Russian bourgeois-democratic revolution of1905-1907. The article recounts the systemic features of the pre-revolutionary periodic press and the peculiarities of the typological analysis of newspapers and magazines published at that time. The research is based on the principles of historical analysis and on the knowledge of the aims and objectives of the press management subject, as well as the needs and interests of the management object.